Storm Surge Modelling for Vietnam’s Coast - Vu Thi Thu Thuy (UNESSCO IHE, 2020)
Vietnam is located near the Northwest Pacific Ocean - the largest storm basin of the world. Thus, Vietnam’s coast with many coastal works, economical zones as well as high density populated regions, is the most vulnerable area under typhoons accompanied with serious storm surges. This is the main reason for the huge damages occuring in the areas. Storm surges threaten not only safety of people’s lives but also coastal structures. Traditional planning, design of coastal projects and coastal zone management usually take into account these effects based on their probability distribution of very limited observed data, which results in a low reliability and safety. Therefore, improving the accuracy in determination of these abnormal water level rise during storm is essential for proper planing, design of coastal works as well as integrated coastal zone management